Labile hypertension in the clinic - Nil Özyüncü; Nail Çağlar (KARE Publishing, 2019)
Labile hypertension is a common problem in daily clinical practice. It is defined as a rapid, temporary rise in blood pressure to above 140/90 mm Hg, most often due to emotional stress, followed by a return to normal values. In the clinical setting, it may be due to white coat hypertension, masked hypertension, pseudopheochromocytoma, orthostatic hypertension, or supine hypertension. Labile hypertension can lead to increased cardiovascular risk. Ambulatory blood pressure monitoring is often used for the diagnosis. Alpha blockers+beta blockers and antidepressants are frequently used for treatment.